Feasibility of Bariatric Surgery as a Strategy for Secondary Prevention in Cardiovascular Disease: A Report from the Swedish Obese Subjects Trial - Lotta Delling; Kristjan Karason; Torsten Olbers; David Sjöström; Björn Wahlstrand; Björn Carlsson; Lena Carlsson; Kristina Narbro; Jan Karlsson; Carl Johan Behre; Lars Sjöström; Kaj Stenlöf (Hindawi Limited, 2010)
Aims. Evaluation of bariatric surgery as secondary prevention in obese patients with ischemic heart disease (IHD). Methods. Analysis of data from 4047 subjects in the Swedish Obese Subjects (SOSs) study. Thirty-five patients with IHD are treated with bariatric surgery (𝑛=21) or conventional treatment (𝑛=14). Mean follow-up is 10.8 years. Results. Bariatric surgery resulted in sustained weight loss during the study period. After 2 years, the surgery group displayed significant reductions in cardiovascular risk factors, relief from cardiorespiratory symptoms, increments in physical activity, and improved quality of life. After 10 years, recovery from hypertension, diabetes, physical inactivity, and depression was still more common in the surgery group. There were no signs of increased cardiovascular morbidity or mortality in the surgery group. Conclusion. Bariatric surgery appears to be a safe and feasible treatment to achieve long-term weight loss and improvement in cardiovascular risk factors, symptoms, and quality of life in obese subjects with IHD.